2020
DOI: 10.3390/ijms21207730
|View full text |Cite
|
Sign up to set email alerts
|

Human Amniotic Epithelial Stem Cells: A Promising Seed Cell for Clinical Applications

Abstract: Perinatal stem cells have been regarded as an attractive and available cell source for medical research and clinical trials in recent years. Multiple stem cell types have been identified in the human placenta. Recent advances in knowledge on placental stem cells have revealed that human amniotic epithelial stem cells (hAESCs) have obvious advantages and can be used as a novel potential cell source for cellular therapy and clinical application. hAESCs are known to possess stem-cell-like plasticity, immune-privi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 177 publications
1
33
0
Order By: Relevance
“…Consistent with our data, in a mouse model of perinatal brain injury, hAEC-CM was effective at reducing injury severity by decreasing the percentage of neural apoptosis (Leaw et al, 2017). Meng et al and Sankar et al showed that hAECs can promote the survival of neurons and alter the microenvironment for neural repair (Qiu et al, 2020). Also, the hAEC-CM was found to have neurotrophic effects in a spinal cord injury (Nguyen et al, 2010;Jayapal et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with our data, in a mouse model of perinatal brain injury, hAEC-CM was effective at reducing injury severity by decreasing the percentage of neural apoptosis (Leaw et al, 2017). Meng et al and Sankar et al showed that hAECs can promote the survival of neurons and alter the microenvironment for neural repair (Qiu et al, 2020). Also, the hAEC-CM was found to have neurotrophic effects in a spinal cord injury (Nguyen et al, 2010;Jayapal et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…Also, vitamin C was reported to promote hAC proliferation ( 17 ). Usually, DMEM supplemented with 10% FBS and 10 ng/ml of epidermal growth factor (EGF) is used ( 26 ), but certain medium modifications can stimulate hAC differentiation into cells of different germ layers ( 27 ). We used TeSR2, a serum-free medium dedicated to stem cells and free of complementary growth factors, such as EGF.…”
Section: Discussionmentioning
confidence: 99%
“…hAECs are a heterogeneous epithelial population that originates from the lining of the inner membrane of the placenta which provides an abundant cellular source for stem cell-based therapy (Miki et al, 2005). In comparison to other sources of stem cells, gestational tissue gives great advantages including easy collection without the need for invasive methods (Qiu et al, 2020). Large numbers of hAECs can be isolated from the placenta after birth, thus bypassing ethical barriers and resulting in an abundance of immediately available, primary (non-cultured) cells to be used therapeutically.…”
Section: Human Amniotic Epithelial Cellsmentioning
confidence: 99%
“…hAECs have immense potential to safely reduce the burden of many serious diseases and injuries to different organs, including the kidney, due to their unique properties (Ren et al, 2020). They possess some degree of plasticity, immune privilege, non-tumorigenicity, anti-infection/cancer properties, and lack of ethical concerns and paracrine properties that are essential to their potential therapeutic applications in immune-mediated diseases (Qiu et al, 2020).…”
Section: Human Amniotic Epithelial Cellsmentioning
confidence: 99%